Answer:
[tex]p(x)=-5(x-12)^2+405[/tex]
Step-by-step explanation:
Hi there!
Vertex form: [tex]f(x)=a(x-h)^2+k[/tex]
[tex]p(x)=-5x^2+120x-315[/tex]
Factor out -5 from the first two terms
[tex]p(x)=-5(x^2-24x)-315[/tex]
Complete the square by adding [tex](\frac{24}{2} )^2[/tex] (the square of half of the x-coefficient)
[tex]p(x)=-5(x^2-24x+(\frac{24}{2} )^2)-315-(-5)(\frac{24}{2} )^2[/tex]
We're subtracting [tex](-5)(\frac{24}{2} )^2[/tex] because we need to keep the equation balanced and we can't just add new values.
Complete the square
[tex]p(x)=-5(x-(\frac{24}{2} ))^2-315-(-5)(\frac{24}{2} )^2[/tex]
Simplify
[tex]p(x)=-5(x-12)^2-315+720\\p(x)=-5(x-12)^2+405[/tex]
Summary:
I hope this helps!